Hubungan Persepsi Citra Tubuh dan Pengetahuan Gizi Seimbang dengan Status Gizi Lebih Siswa SMA di Wilayah Kerja Puskesmas Teluk Dalam - Gregory Stevanus Gultom; Triawanti Triawanti; Ida Yuliana (Homeostasis, 2020)
Abstract: Obesity is an overweight condition as a result of an accumulation of body fat. Data from Riskesdas in 2018 showing the prevalence of overweight and obese population aged 16-18 years in South Kalimantan Province reached 8.9% for overweight and 3.2% for obese. Some factors that cause obesity in adolescents are the body image perception and balanced nutritional knowledge. The study aims to determine the association between body image perception and balanced nutrition knowledge with the over nutritional status of high school students in the Teluk Dalam community health centre work area. This study used an analytic observational method with a case-control approach. The sample of this study was students with over nutritional status (case group) and normal nutritional status (controlled group) based on data from the Teluk Dalam community health centre in Banjarmasin in the 2018 period using a random sampling technique. Data analysis used the chi-square test with 95% confident interval. The results of this study in the case group contained 44.4% having a positive body image, 55.6% negative body image, 58.3% lack of balanced nutritional knowledge, 8.3% with adequate balanced nutritional knowledge, and 33.3% with well-balanced nutritional knowledge. While in the control group we found 94.4% having a positive body image, 5.6% negative body image, 13.9% lacking balanced nutrition knowledge, 25% adequate balanced nutrition knowledge, and 61.1% well balanced nutrition knowledge. The results of the chi-square analysis showed that there were ann associations between the body image perception (p = 0,000 OR = 21.25) and balanced nutritional knowledge (p = 0,000) with the over nutritional status of high school students in the Teluk Dalam community health centre work area. Keywords: perception, body image, knowledge, balanced nutritional, nutritional status, adolescents Abstrak: Obesitas adalah kelebihan berat badan sebagai akibat dari penimbunan lemak tubuh. Data Riskesdas tahun 2018, prevalensi gemuk dan obesitas penduduk dengan umur 16-18 tahun di Provinsi Kalimantan Selatan mencapai 8,9% gemuk dan 3,2% obesitas. Beberapa faktor yang menyebabkan terjadinya obesitas pada remaja yaitu persepsi citra tubuh dan pengetahuan gizi seimbang. Penelitian bertujuan mengetahui hubungan persepsi citra tubuh dan pengetahuan gizi seimbang dengan status gizi lebih siswa SMA di wilayah kerja Puskesmas Teluk Dalam. Metode penelitian observasional analitik dengan pendekatan case control. Sampel penelitian adalah siswa dengan status gizi lebih (kelompok kasus) dan status gizi normal (kelompok kontrol) berdasarkan data Puskesmas Teluk Dalam Banjarmasin periode 2018. Pengambilan sampel dengan simple random sampling. Analisis data mengguanakan uji chi-square dengan derajat kepercayaan 95%. Hasil penelitian ini pada kelompok kasus terdapat 44,4% memiliki citra tubuh positif, 55,6% citra tubuh negatif, 58,3% pengetahuan gizi seimbang kurang, 8,3% pengetahuan gizi seimbang cukup, dan 33,3% pengetahuan gizi seimbang baik. sedangkan kelompok kontrol terdapat 94,4% memiliki citra tubuh positif, 5,6% citra tubuh negatif, 13,9% pengetahuan gizi seimbang kurang, 25% pengetahuan gizi seimbang cukup, dan 61,1% pengetahuan gizi seimbang baik. Hasil analisis uji chi square menunjukkan terdapat hubungan antara persepsi citra tubuh (p=0,000 OR=21,25) dan pengetahuan gizi seimbang (p=0,000) dengan status gizi lebih siswa SMA di wilayah kerja Puskesmas Teluk Dalam. Kata-kata kunci: persepsi, citra tubuh, pengetahuan, gizi seimbang, status gizi, remaja